An Open Source Solution for “Hands-on” teaching of PET/CT to Medical Students under the COVID-19 Pandemic - Biermann, Martin; Kanoun, Salim; Davidsen, Trond; Gray, Robert (Nuklearmedizin - NuclearMedicine, 2020)
Aims Since 2017, medical students at the University of Bergen were taught PET/CT “hands-on” by viewing PET/CT cases in native format on diagnostic workstations in the hospital. Due to the COVID-19 pandemic, students were barred access. This prompted us to launch and evaluate a new freeware PET/CT viewing system hosted in the university network.Methods We asked our students to install the multiplatform Fiji viewer with Beth Israel PET/CT plugin (http://petctviewer.org) on their personal computers and connect to a central image database in the university network based on the public domain orthanc server (https://orthanc-server.com). At the end of course, we conducted an anonymous student survey.Results The new system was online within eight days, including regulatory approval. All 76 students (100 %) in the fifth year completed their course work, reading five anonymized PET/CT cases as planned. 41 (53 %) students answered the survey. Fiji was challenging to install with a mean score of 1.8 on a 5-point Likert scale (5 = easy, 1 = difficult). Fiji was more difficult to use (score 3.0) than the previously used diagnostic workstations in the hospital (score 4.1; p < 0.001, paired t-test). Despite the technical challenge, 47 % of students reported having learnt much (scores 4 and 5); only 11 % were negative (scores 1 and 2). 51 % found the PET/CT tasks engaging (scores 4 and 5) while 20 % and 5 % returned scores 2 and 1, respectively.Conclusion Despite the initial technical challenge, “hands-on” learning of PET/CT based on the freeware Fiji/orthanc PET/CT-viewer was associated with a high degree of student satisfaction. We plan to continue running the system to give students permanent access to PET/CT cases in native format regardless of time or location.
Keywords: nuclear medicine; PET/CT; e-learning; medical education